Dunia Geometri 3D: Developing an AR-Integrated Website to Enhance Students' Conceptual Understanding of Spatial Geometry - Azizah, Mazia; Lisnani, Lisnani; Alia, Hilma; Rizwan, Muhammed; Renanda, Ana (Mosharafa: Jurnal Pendidikan Matematika, 2025)
Penelitian ini mengembangkan media pembelajaran berbasis website terintegrasi multimedia interaktif untuk materi bangun ruang menggunakan model ADDIE (Analysis, Design, Development, Implementation, Evaluation) dengan subjek penelitian siswa SMP kelas VII yang berjumlah 34 orang. Instrumen penelitian mencakup angket dan tes. Teknik analisa data berdasarkan analisis kevalidan, kepraktisan, dan keefektifan media yang dikembangkan. Website "Dunia Geometri 3D" mengintegrasikan visualisasi 3D, video pembelajaran, pameran virtual AR Step, quiz interaktif Google Form, dan game edukatif Wordwall. Hasil penelitian ini yaitu media pembelajaran berbasis website terintegrasi multimedia interaktif untuk materi bangun ruang yang valid, praktis, dan efektif. Analisis peningkatan pemahaman konsep menggunakan uji N-Gain menunjukkan skor 0,45 dengan kategori sedang, mengindikasikan bahwa media pembelajaran ini efektif meningkatkan pemahaman konsep geometri ruang siswa secara signifikan. Media pembelajaran ini berkontribusi terhadap transformasi pembelajaran geometri di era digital dengan memfasilitasi literasi digital dan pembelajaran mandiri abad 21. This study developed a website-based learning media integrated with interactive multimedia for spatial geometry material using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model with 34 seventh-grade junior high school students as research subjects. The research instruments included questionnaires and tests. Data analysis techniques were based on the analysis of the validity, practicality, and effectiveness of the developed media. The "Dunia Geometry 3D" website integrates 3D visualization, learning videos, AR Step virtual exhibitions, interactive Google Form quizzes, and Wordwall educational games. The results of this study are website-based learning media integrated with interactive multimedia for spatial geometry material that is valid, practical, and effective. Analysis of the increase in conceptual understanding using the N-Gain test showed a score of 0.45 in the moderate category, indicating that this learning media is effective in significantly improving students' understanding of spatial geometry concepts. This learning media contributes to the transformation of geometry learning in the digital era by facilitating digital literacy and independent learning in the 21st century.